Influence Of Perceived Stress And Emotional Intelligence On Resilience: A Correlational Study Among Indian Corporate Freshers - Ghadge, Charusheela; Srivastava, Kiran (Journal of Neonatal Surgery, 2025)
Transition from academic life to professional job marks a major life change. This change to corporate landscape can be often overwhelming with a series of challenges and stressors. Enhanced workplace support systems are necessary to reduce the prevalent stress experienced by freshers in initial phase of their professional careers. This study investigates influence of Perceived stress (PS), Emotional Intelligence (EI) and Resilience amongst Indian corporate freshers. A sample of 120 corporate freshers was surveyed using validated instruments including the Perceived Stress Scale (PSS), Emotional Intelligence Scale (EIS), along with Brief Resilience Scale (BRS). In current quantitative study, cross-sectional correlational design was employed for assessing influence of perceived stress and emotional intelligence on resilience. The outcomes indicated that perceived stress is negatively associated with resilience (r=-0.45, p=0.001) since individuals are less resilient when they perceive higher levels of stress. Emotional intelligence and resilience demonstrated a moderate positive correlation (r=0.52, p<0.001), suggesting higher emotional intelligence corresponds with greater resilience. Multiple regression showed emotional intelligence has a stronger positive influence on resilience (coefficient=0.40, p<0.001) than negative impact of perceived stress (coefficient=-0.35, p=0.002). The results show a moderate relationship between perceived stress, resilience, and emotional intelligence since emotional intelligence is an essential factor in minimizing stress impacts. In general, this research provides greater understanding regarding emotional intelligence as a counteractive tool to stress effects and resilience building for early career professionals.